HUBUNGAN INTENSITAS PENGGUNAAN SMARTPHONE DENGAN KUALITAS HIDUP PADA MAHASISWA FAKULTAS KEDOKTERAN UNIVERSITAS ISLAM AL-AZHAR ANGKATAN 2019 - Ni Ketut Yulina Pratiwi; Yolly Dahlia; Baiq Novaria Rusmaningrum; Dian Rahadianti (Yayasan Nusantara Hasana Berdikari, 2023)
Students of the Faculty of Medicine, Al-Azhar Islamic University, since the pandemic, lecture activities have been carried out using an online system so that the use of smartphones will certainly increase. Besides that, most students will use smartphones as a diversion of boredom which makes students use smartphones outside of academics with high intensity so that it has a negative effect, both from disrupting concentration, sleep quality to interfering with their quality of life. Research objectives to find out the relationship between the intensity of smartphone use and the quality of life of students of the Al-Azhar Islamic University Faculty of Medicine class of 2019. Research method observational analytic research with a cross-sectional study design. The sampling technique used purposive sampling. The research was conducted at the Al-Azhar Islamic University Medical Faculty on January 21, 2023. The research sample was 81 respondents. The data obtained were analyzed using the chi-square correlation test. The results showed that the intensity of smartphone use was high with a very bad quality of life, namely 25 (30.9%) and respondents who had a low intensity of smartphone use with a very bad quality of life, namely 4 (4.9%). Based on the results of the analysis using Chi Square, a p-value of 0.006 (p-value <0.05) means that Ho is rejected, thus indicating that there is a relationship between the intensity of smartphone use and the quality of life of FK Unizar students Class of 2019 Conclusion: There is a relationship between the intensity of smartphone use and quality of life.